Prevalence of intestinal schistosomiasis in pre-school aged children: a pilot survey in Marolambo District, Madagascar - Caitlin Sheehy; Heather Lawson; Emmanuel H. Andriamasy; Hannah J. Russell; Alice Reid; Gina U. Raderalazasoa; Graham Dodge; Robbie Kornitschky; James M. StJ. Penney; Tahiry N. Ranaivoson; Antsa Andrianiaina; Jenny S. Emmanoela; et al. (BMC, 2021)
Abstract School-aged children (SAC) have a considerable burden of intestinal schistosomiasis in Madagascar yet its burden in pre-school aged children (PSAC) is currently overlooked. To assess the at-risk status of PSAC, we undertook a pilot epidemiological survey in June 2019 examining children (n = 89), aged 2-4-years of balanced gender, in six remote villages in Marolambo District, Madagascar. Diagnosis included use of urine-circulating cathodic antigen (CCA) dipsticks and coproscopy of stool with duplicate Kato-Katz (K-K) thick smears. Prevalence of intestinal schistosomiasis by urine-CCA was 67.4% (95% confidence interval [CI]: 56.5-77.2%) and 35.0% (95% CI: 24.7-46.5%) by K-K. The relationship between faecal eggs per gram (epg) and urine-CCA G-scores (G1 to G10) was assessed by linear regression modelling, finding for every increment in G-score, epg increased by 20.4 (6.50-34.4, P = 0.006). Observed proportions of faecal epg intensities were light (78.6%), moderate (17.9%) and heavy (3.6%). Soil-transmitted helminthiasis was noted, prevalence of ascariasis was 18.8% and trichuriasis was 33.8% (hookworm was not reported). Co-infection of intestinal schistosomiasis and soil-transmitted helminthiasis occurred in 36.3% of PSAC. These results provide solid evidence highlighting the overlooked burden of intestinal schistosomiasis in PSAC, and they also offer technical  guidance for better surveillance data for the Madagascan national control programme.